DAMAGE CAUSED BY A WHEELED HARVESTER TO THE RESIDUAL TREES OF A PINUS STAND IN THE FIRST MECHANIZED MIXED THINNING - Diniz, Carlos Cezar Cavassin; Oliveira, Felipe Martins de; Timofeiczyk Junior, Romano; Robert, Renato Cesar Gonçalves; Tramontini, Miguel Pesch; Brito, Fabio Cordeiro de (Floresta, 2020)
The objective of this study was to evaluate the damage caused to the remaining trees of a pinus stand submitted to mechanized thinning by a wheeled harvester. The data were obtained in the operational areas of timber harvesting in a forest company located in the city of Inácio Martins, in the state of Paraná, Brazil. The Pinus stand of the study was 11 years old, and was submitted to the first commercial thinning. The operation was performed by a harvester, characterized by the systematic removal of the 5th planting line to give access to the interior of the stand, followed by selective thinning in the individuals demarcated in the two lines adjacent to the traffic trails. The damage caused to the remaining trees of the stand regarding their numbers, dimensions and location in relation to the harvester’s operation track was evaluated, and the data were analyzed using the Profile Analysis multivariate analysis technique. It was observed that 25% of the remaining trees suffered some kind of damage, being considered a high value, but current to the literature. It was evidenced that the section of the tree in need of greater alert was the base because damages in greater intensity and dimensions were observed to it, which can bring future losses to the stand. Thus, a need for improvements in operational procedures was demonstrated.